2005
DOI: 10.1007/s11664-005-0267-2
|View full text |Cite
|
Sign up to set email alerts
|

A CdTe passivation process for long wavelength infrared HgCdTe photo-detectors

Abstract: Passivant-Hg 1-x Cd x Te interface has been studied for the CdTe and anodic oxide (AO) passivants. The former passivation process yields five times lower surface recombination velocity than the latter process. Temperature dependence of surface recombination velocity of the CdTe/n-HgCdTe and AO/nHgCdTe interface is analyzed. Activation energy of the surface traps for CdTe and AO-passivated wafers are estimated to be in the range of 7-10 meV. These levels are understood to be arising from Hg vacancies at the HgC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 28 publications
0
13
0
2
Order By: Relevance
“…As a forward scan direction, we took the variation in the voltage from negative to positive values, and as the re− verse direction, from positive to negative values. We studied the capacitance−voltage characteristics of MIS−structures with the composition in the working layer 0.22-0.23 at passivation only CdTe, and also MIS−struc− tures with two−layer low−temperature insulator SiO 2 It is shown that the grown in situ CdTe forms the high quality interface with Hg 1-x Cd x Te. The density of surface states in the middle of the forbidden gap in system Hg 0.78 Cd 0.22 Te is equal to (1.4-2.8)×10 11 eV -1 cm -2 , the density of fixed charges composed (1.3-1.7)×10 -8 Cl/cm 2 , and density of mobile charges does not exceed 10 -10 Cl/cm 2 .…”
Section: Samples and Methodsmentioning
confidence: 99%
“…As a forward scan direction, we took the variation in the voltage from negative to positive values, and as the re− verse direction, from positive to negative values. We studied the capacitance−voltage characteristics of MIS−structures with the composition in the working layer 0.22-0.23 at passivation only CdTe, and also MIS−struc− tures with two−layer low−temperature insulator SiO 2 It is shown that the grown in situ CdTe forms the high quality interface with Hg 1-x Cd x Te. The density of surface states in the middle of the forbidden gap in system Hg 0.78 Cd 0.22 Te is equal to (1.4-2.8)×10 11 eV -1 cm -2 , the density of fixed charges composed (1.3-1.7)×10 -8 Cl/cm 2 , and density of mobile charges does not exceed 10 -10 Cl/cm 2 .…”
Section: Samples and Methodsmentioning
confidence: 99%
“…We studied the capacitance−voltage characteristics of MIS−structures with the composition in the working layer 0.22-0.23 at passivation only CdTe, and also MIS−struc− tures with two−layer low−temperature insulator SiO 2 It is shown that the grown in situ CdTe forms the high quality interface with Hg 1-x Cd x Te. The density of surface states in the middle of the forbidden gap in system Hg 0.78 Cd 0.22 Te is equal to (1.4-2.8)×10 11 eV -1 cm -2 , the density of fixed charges composed (1.3-1.7)×10 -8 Cl/cm 2 , and density of mobile charges does not exceed 10 -10 Cl/cm 2 .…”
Section: Samples and Methodsmentioning
confidence: 99%
“…Consequently, it is necessary to passivate the surface of CMT in order to reduce these surface currents as well as to maintain electrical and chemical stability. The physical and chemical properties of CdTe are very suitable for use as passivation materials for CMT [1,2]. Considering the various characteristics such as bandgap, crystal struc− ture, chemical binding, phase diagram, electrical properties, adhesion, growth methods and infrared transmission it is concluded that CdTe have emerged as strong candidate for passivation of CMT devices.…”
Section: Introductionmentioning
confidence: 99%
“…Creation of such layers can improve the thre− shold characteristics of infrared detectors based on HgCdTe by reducing the influence of the surface recombination on the lifetime of photocarriers in the volume of the epitaxial film [5]. Characteristics of detectors based on HgCdTe lar− gely depend on the parameters of the insulator passivation coatings and their interfaces with the semiconductor [7,8], as well as on the mechanisms of generation of charge car− riers in the space charge region [4]. Therefore, investigation of the characteristics of metal−insulator−semiconductor structures (MIS structures) based on heteroepitaxial MBE HgCdTe remains an actual task.…”
Section: Introductionmentioning
confidence: 99%